DEVELOPMENT OF PODCAST LEARNING MEDIA ABOUT EDUCATIONAL RESEARCH METHODS FOR MECHANICAL ENGINEERING EDUCATION STUDENTS - Basuki Wibawa; Imam Mahir; Anardratama Muhammad Owen (Department of Mechanical Engineering Education, 2025)
This research aims to develop a podcast-based audiovisual learning media on the basic concept of educational research methods for students of the Department of Mechanical Engineering Education, Faculty of Engineering, UNJ, with its validation tested by material experts, media experts, and student responses. This study uses the Research & Development (R&D) research method with the ADDIE model: Analysis, Design, Development, Implementation, Evaluation. Product validation was carried out by one material expert, one media expert, and two practice-question-grid experts. To measure the increase in student understanding by using this product, the Gain Normalization calculation formula is used. The validation results showed a 94% score from material experts and media experts, categorized as 'Very Valid'. The practicality test showed an 88% score, while the N-Gain was 59% ('Quite Effective'). In conclusion, the developed podcast-based audiovisual learning media is highly valid and suitable as a learning resource for Research Methodology courses.